Penyelesaian Sengketa Pemberhentian Ekspor Nikel Indonesia ke Uni Eropa oleh World Trade Organization - Rachma Putri; Sintya Widiesty; Ajie Danto Wicaksono (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2022)
This article aims to analyze how the role of the World Trade Organization (WTO) in resolving disputes over the termination of Indonesia's nickel exports to the European Union. Nickel has long been known as Indonesia's strategic commodity. After the establishment of the Asosiasi Penambang Nikel Indonesia (APNI) in 1901 nickel began to be managed for export activities. However, the Indonesian government through the policy of President Joko Widodo stopped exporting low grade nickel with a value of 1.7% to European Union countries. Therefore, the European Union also reports the policy of stopping exports to its country to the WTO free trade regime which has the right to regulate. Other countries did not respond like the European Union because Indonesian nickel is very important for the European Union. The research method used is descriptive research method with a qualitative approach. In collecting data, the author team used literature studies in the form of books, online journals, online articles that are relevant to the research topic. The findings of this study are that the settlement of disputes over the termination of Indonesia's nickel exports to the European Union is at the consultation stage at the WTO. The European Union has actually not accepted nickel exports from Indonesia for a long time and the European Union reporting action was actually carried out because the stainless steel and automotive industries that use nickel experienced a decline in interest, due to losing competitiveness with the Tiongkok state industry.